Impact Work Motivation and Perceived Coworker Support on Organizational Commitment At Human Resources Development and Management Agency - Iskandar Nordat; Burhanuddin Tola; Mahmuddin Yasin (Journal of International Conference Proceedings (JICP), 2019)
Organizational commitment can be seen from various aspects related as individuals to the organization based on salary, social status and preferences for their work. This study aims to find causal relationships between variables (work motivation, perceived coworker support on organizational commitment). This study used 158 employee at HRD & Management Agency in Indonesia. The results show that work motivation has a significant and positive effect on organizational commitment by 0.462. Perceived coworker support also has a significant and positive effect on organizational commitment by 0.387. HRD & Management Agency in Indonesia must provide work motivation to employees because it has a greater influence than perceived coworker support on increasing organizational commitment.